PENERAPAN METODE YANBU’A DALAM PEMBELAJARAN BACA AL- QUR’AN PADA ANAK USIA DINI DI TK NURUL ULUM RAMBANG MUARA ENIM - Nike Affin Ni’mah; Anwar Sa'dullah; Eko Setiawan (UNISMA, 2022)
Learning the Method of Reading the Quran which is carried out at Nurul Ulum Rambang Muara Enim Kindergarten is currently still difficult to apply learning that suits the needs of children. So far, nurul Ulum Rambang Muara Enim Kindergarten still uses the traditional method, namely the iqro' method, although the iqro' method is good for learning the Quran, but requires a new innovation and adapts to the comprehension ability of each individual child. The purpose of this study is to determine the application of the Yanbu'a method in reading the Quran in early childhood. The research method used is a qualitative research method, with a type of case study research where the subject used in the research is students at Nurul Ulum Rambang Muara Enim Kindergarten for the 2021/2022 academic year. In accordance with the data analysis, the results of the study were obtained that the yanbu'a method for early childhood in Nurul Ulum Kindergarten was very influential, this was due to the use of a very clear method regarding the beginning of the location of the letter makhorijul, short long information, and there are 7 volumes of application but each volume is measured by the level of ability of the child. From the results of the study, it was concluded that the application of the yanbu'a method in learning the Quran in early childhood in Nurul Ulum Kindergarten can help improve children's ability to learn the Quran.